Stratospheric Communication of El Nino Teleconnections to European Winter - Bell, C; Gray, L; Charlton-Perez, A; Joshi, M; Scaife, A (Journal of Climate, 2016)
The stratospheric role in the European winter surface climate response to El Niño-Southern Oscillation sea surface temperature forcing is investigated using an intermediate general circulation model with a well-resolved stratosphere. Under El Niño conditions, both the modeled tropospheric and stratospheric mean-state circulation changes correspond well to the observed "canonical" responses of a late winter negative North Atlantic Oscillation and a strongly weakened polar vortex, respectively. The variability of the polar vortex is modulated by an increase in frequency of stratospheric sudden warming events throughout all winter months. The potential role of this stratospheric response in the tropical Pacific-European teleconnection is investigated by sensitivity experiments in which the mean state and variability of the stratosphere are degraded. As a result, the observed stratospheric response to El Niño is suppressed and the mean sea level pressure response fails to resemble the temporal and spatial evolution of the observations. The results suggest that the stratosphere plays an active role in the European response to El Niño. A saturation mechanism whereby for the strongest El Niño events tropospheric forcing dominates the European response is suggested. This is examined by means of a sensitivity test and it is shown that under large El Niño, forcing the European response is insensitive to stratospheric representation.